Effect of benzalkonium chloride on the stability of the precorneal tear film in rabbit and man. - Wilson, W. S. (1975)
Benzalkonium chloride, a surface-active preservative commonly used in eyedrop preparations, has been shown to hasten the drying of the precorneal tear film. In the rabbit, 0.01 per cent benzalkonium (the concentration usually employed as a preservative) shortened the time required for the appearance of dry spots on the corneal surface by a factor of about four. In man, an approximately twofold hastening was demonstrated. This effect is thought to preclude the use of this substance as a preservative in eyedrop preparations for use as local anaesthetics.